2015
DOI: 10.1016/j.ajpath.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Xenograft Models for Pancreatic Adenocarcinoma Demonstrate Retention of Tumor Morphology through Incorporation of Murine Stromal Elements

Abstract: Direct implantation of viable surgical specimens provides a representative preclinical platform in pancreatic adenocarcinoma. Patient-derived xenografts consistently demonstrate retained tumor morphology and genetic stability. However, the evolution of the tumor microenvironment over time remains poorly characterized in these models. This work specifically addresses the recruitment and incorporation of murine stromal elements into expanding patient-derived pancreatic adenocarcinoma xenografts, establishing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 17 publications
5
94
0
1
Order By: Relevance
“…It is now well established that human tumour stromal cells are replaced by mouse counterparts following engraftment 155 . As a consequence of this substitution, species-specific RNA sequencing-based expression profiling of PDXs offers a unique opportunity to distinguish mouse stroma-derived transcripts from human cancer cell-derived transcripts without the need to physically separate the two components before RNA extraction.…”
Section: Modelling Metastatic Disease Subcutaneous Transplantation Umentioning
confidence: 99%
“…It is now well established that human tumour stromal cells are replaced by mouse counterparts following engraftment 155 . As a consequence of this substitution, species-specific RNA sequencing-based expression profiling of PDXs offers a unique opportunity to distinguish mouse stroma-derived transcripts from human cancer cell-derived transcripts without the need to physically separate the two components before RNA extraction.…”
Section: Modelling Metastatic Disease Subcutaneous Transplantation Umentioning
confidence: 99%
“…21 Briefly, a viable portion of resected tissue 2 Â 2 mm in size was isolated immediately from surgically resected primary PC specimens with care to minimize critical ischemia time. PC tissue was then implanted subcutaneously into an 8-weekold female nonobese diabetic.Cg-Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mouse (The Jackson Laboratory, Bar Harbor, ME).…”
Section: Tumor Transplantationmentioning
confidence: 99%
“…17,21 Specifically, here, we demonstrate the expansion of human PCCs through a PDX model that preserves the tumor heterogeneity with a 100% success rate. These established PDX-derived primary cell lines display uniform markers associated with a human PC origin with retained tumorigenicity.…”
mentioning
confidence: 99%
“…Tumor fragments used to establish PDTX models contain tumor and stromal cells, as well as the extracellular matrix. Human stroma is detectable in early passages, but it is completely replaced along transplantations by mouse stroma [25,51]. In fact, recent studies clearly demonstrated how murine cells functionally replaced human stroma to recreate malignant niches closely mimicking the original human tumor microenvironment.…”
Section: Pdtx As a Tool To Explore Microenvironmentmentioning
confidence: 99%